Effect of Temperature, pH and Salinity on carotenoid production in Rodotorula mucilaginosa - Naghavi, FarzanehSadat; Hanachi, Parichehr; Saboora, Azra (Research in Biotechnology, 2014)
Rhodotorula mucilaginosa, is a species of heterobasidiomycetous yeasts which is able to produce carotenoid pigments. The optimum conditions for carotenoid production of this strain in shaking flask cultivation were a temperature of 30 ÃŒÅ C and initial pH value of 5.0 in a medium of glucose 10 g/L, (NH4)2SO4 2 g/L, KH2 (PO4) 2 g/L, MgSO4.7H2O 0.5 g/L, CaCl2.2H2O 0.1 g/L, yeast extract 1 g/L. This study demonstrated that this strain failed to produce pigments in any amounts of sea salt.